PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR CAMAT LUBUK DALAM KABUPATEN SIAK - Hendra Budiman; Sri Indarti; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at the Kantor Camat Lubuk Dalam KabupatenSiak. The samples in this study were as many as 33 employees Kantor Camat Lubuk Dalam Kabupaten Siak and entirely sampled so this is a research study census. The purpose of this study was to determine the effect of partial and simultaneous competence and leadership to employee performance in Kantor Camat Lubuk Dalam Kabupaten Siak. Based on the results of the study showed that the competence variable (X1) partially affect the performance, leadership variable (X2) partially no effect on performance and competence variables (X1) and the leadership variable (X2) simultaneously affect the performance of employees at Kantor Camat Lubuk Dalam Kabupaten Siak. The suggestion is to employees in order to increase its competence in a way more confidence and always implement systematic steps to solve a problem that occurs on the job. And are expected to maintain an attitude of leadership that leadership in a way more attention to his subordinates and show friendly attitude that strengthen social relationships between leaders and subordinates. Also expected leaders to constantly improve performance employees at Kantor Camat Lubuk Dalam Kabupaten Siak by supporting subordinates in improving the quality of work.Keywords : Competence, Leadership, Performance.